2013
DOI: 10.1093/eurheartj/eht369
|View full text |Cite
|
Sign up to set email alerts
|

Improved long-term clinical outcomes in patients with ST-elevation myocardial infarction undergoing remote ischaemic conditioning as an adjunct to primary percutaneous coronary intervention

Abstract: Remote ischaemic conditioning before primary percutaneous coronary intervention seemed to improve long-term clinical outcomes in patients with ST-elevation myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
199
4
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(213 citation statements)
references
References 23 publications
7
199
4
3
Order By: Relevance
“…The absence in change of hemodynamic recovery in our study is in accordance with previous studies testing Rotigaptide and the new analogue danegaptide [1][2][3][4][5][6][7][8][9][10][11][12][13]20,[42][43][44]. Although we did not observe statistically significant changes in post-ischemic hemodynamic outcome between the different groups the pattern followed the expected responses according to infarct size reduction.…”
Section: Baselinesupporting
confidence: 92%
See 1 more Smart Citation
“…The absence in change of hemodynamic recovery in our study is in accordance with previous studies testing Rotigaptide and the new analogue danegaptide [1][2][3][4][5][6][7][8][9][10][11][12][13]20,[42][43][44]. Although we did not observe statistically significant changes in post-ischemic hemodynamic outcome between the different groups the pattern followed the expected responses according to infarct size reduction.…”
Section: Baselinesupporting
confidence: 92%
“…Combined acute ischemia and reperfusion injury may lead to irreversible tissue injury and cell death and determines final infarct size. Protecting the heart beyond the myocardial salvage achieved by early revascularization is crucial as infarct size is directly linked to patient outcome [1].…”
Section: Introductionmentioning
confidence: 99%
“…Remote ischemic conditioning by repetitive limb ischemia/reperfusion also reduces myocardial damage in patients undergoing elective interventional2 or surgical coronary revascularization3, 4, 5, 6 and in those with reperfused acute myocardial infarction 7, 8, 9, 10, 11, 12, 13. Cardioprotection was confirmed by reduced release of cardiac biomarkers2, 3, 4, 5, 6, 10 or by increased salvage in cardiac imaging7, 8, 9, 11 but also resulted in improved short‐5, 8 and more long‐term2, 4, 13, 14, 15 clinical outcome in retrospective analyses. Recently, the first prospective, randomized trial on patients with reperfused acute myocardial infarction confirmed improved clinical outcome as a primary end point of remote ischemic conditioning during follow‐up for 3.6 years 13.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sloth et al [89] published 4-year follow-up data on our original study, showing that the improved myocardial salvage translates into clinical prognostic benefit, as MACCE occurred for 17 (13.5%) patients in the RIC treated group compared with 32 (25.6%) patients in the control group, yielding a HR of 0.49 (95%CI: 0.27-0.89, P = 0.018). Furthermore, only 5 deaths (4%) occurred in the intervention group compared with 15 (12%) in the control group, yielding a HR of 0.32 (95%CI: 0.12-0.88, P = 0.027) (Figure 2) [89] . Specific evaluation of death causes suggested a reduction in both cardiac and noncardiac mortality, although only the latter was statistically significantly reduced (and most likely arose by chance).…”
Section: Remote Ischemic Conditioning In Unpredictable Ischemiamentioning
confidence: 96%
“…The authors observed 11 deaths in the control group and only 3 deaths in the RIC group (P = 0.046). The combined endpoint [89] . Eur Heart J (2014) 35: 168-175. pPCI: Primary percutaneous intervention; RIC: Remote ischemic conditioning.…”
Section: Remote Ischemic Conditioning In Predictable Ischemiamentioning
confidence: 99%